High latitutude-living in the emperor penguin: Constraints on foraging and their consequences - Rory Wilson (The Biology of Polar Seas, 2008)
Zimmer, I., Wilson, R. P. (2008). High latitutude-living in the emperor penguin:Constraints on foraging and their consequences. In The Biology of Polar Seas (Ed. Hempel, G., Hempel, I). Springer, Berlin.